Food Additives - Nedra Karunaratne, Desiree; Pamunuwa, Geethi (IntechOpen, 2017)
Food additives is intended to provide the readers with knowledge on some very significant aspects of the food additives currently in use. Food additives have become essential in the food sector with the rising need for food processing and preservation. However, the use of food additives is regulated imposing strict rules as the impact of those additives on health cannot be neglected. The first chapter starts off with a general overview of food additives highlighting the novel trends that enhance the attributes of those additives. Thereafter, the chapters are devoted mainly to plant-derived food additives and microbially derived food additives. The main topics discussed under 'additives from plant origin' are the efficacy of beetroot formulations as a source of nitrate ions, plant-derived food preservatives and plant-derived food additives used in meat and meat-based products. The further chapters discuss 'additives from microbial origin' focusing on lactic acid bacteria and additives derived from lactic acid bacteria and food additives used in 'bread-making'. Overall, this manuscript emphasises the concept of 'clean labelling' and the importance of natural food additives.